Validation of Risk Stratification Criteria to Identify Febrile Neonates at Low Risk of Serious Bacterial Infection - Joni E. Rabiner MD; Maya Capua MD; Dina Golfeiz MD; Jamie Shoag MD; Jeffrey R. Avner MD (SAGE Publishing, 2019)
Our objective was to evaluate the accuracy of risk stratification criteria for febrile neonates in the emergency department. This was a retrospective study of febrile neonates ≤56 days of age. Patients were low risk for serious bacterial infection (SBI) if all test results were within normal ranges. Three hundred thirty-eight patients were enrolled with a mean age of 32 (±14) days, and 78 (23%) had SBI: 26 (8%) with bacteremia, 48 (14%) with urinary tract infection, 3 (1%) with meningitis, and 11 (3%) with pneumonia. Risk stratification criteria identified 47 (14%) as low risk, 2 of whom had SBI (both with Group B Streptococcus bacteremia). The sensitivity was 97.4% (95% confidence interval = 91.0% to 99.7%), and the negative predictive value was 95.7% (95% confidence interval = 84.8% to 98.9%). The risk stratification criteria have high sensitivity and high negative predictive value for identifying infants at low risk for SBI. Care must be taken to assure reliable follow-up.